THE CONTRIBUTION OF USING CHART TO STUDENTS’ ACHIEVEMENT IN WRITING CAUSE AND EFFECT PARAGRAPHS - Januar Tumbuan Manurung; Dolli Rotua Sinaga; Ermina Waruwu (STKIP PGRI Jombang, 2020)
This study was attempted to find out the contributions of using chart to students’ achievement in writing cause and effect paragraphs to the third semester of Management students of Universitas Prima Indonesia, Medan, 2019/2020. The research of this study was a quasi experiment design. There were 56 students taken randomly from two classes then divided into two groups; experimental group and control group. The experimental group was taught by using chart to achieve their writing, while control group was taught in a conventional way; without using chart. The collected data were analyzed by using t-test formula. The reliability of the experimental group was 0.42, and the reliability of the control group’s test was 0.74. The analysis showed that the score of the students by using chart were different significantly from those students without using chart. The result of t- calculation showed that t-observe is 9.8 and the t-observe is bigger than t-table (9.8> 1.671 : p = 0.05). It means that using chart significantly contributes the the students’ achievement in writing cause and effect paragraphs. In other words, the hypothesis which said that “there is a significant contribution of using chart to students’ achievement in writing cause and effect paragraphs” is accepted.